Wasatiyyah in the perspective of Muhammad Asad - Ahmad, Nadzrah; Amir, Ahmad Nabil (IIUM, 2017)
This paper aims to analyze Muhammad Asad’s significant ideas and doctrine of wasatiyyah (Islamic moderation) as illustrated in his magnum opus The Message of the Qur’an. It endeavors to discuss the essential idea and principle of moderate Islam or “community of the middle way” (ummah wasata) as interpreted and propounded by Asad (1900-1992) in his Tafsir. It will also analyzed other major works of Asad that presented his views and understanding of wasatiyyah such as The Road to Mecca – his auto-spiritual biography and travelogue, This Law of Ours and Other Essays, The Principles of State and Government in Islam, Islam at the Crossroads and Sahih al-Bukhari: The Early Years of Islam that further illustrated his analytical discussion of this important idea and its significant implications in Muslim society.